A Study of Driving Behavior and Smartphone Usage Among University Students - Md.lazam, Nur Nazhifah; Ahmad Nazri, Darweesh; Mohd Zaidi, Nur Maisarah; Hamid, Nor Baizura (Multidisciplinary Applied Research and Innovation, 2023)
This study was conducted to obtain more accurate and detailed data on driver behavior and smartphone use among university students while driving. A field study about taking speed data using Laser Speed Gun was undertaken to make self-observations on road users from the way from IIUM Pagoh to UTHM Pagoh, Johor. 20 drivers representing 10% drive while using a smartphone. 90% of drivers equivalent to 180 drivers drive by not using a smartphone. A total of 2 female drivers (10%) drove while using a smartphone. A total of 18 male drivers (90%) drove while using a smartphone. It can be concluded that male drivers are more likely to use smartphones than female drivers. 50 university students were interviewed and questioned to gain insight into their perspectives on the usage of smartphones while driving. Drivers should take more proactive actions such as reducing the use of smartphones while driving for the safety of themselves, passengers, and other drivers to prevent unwanted things from happening.